2012
DOI: 10.1089/fpd.2011.1082
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Multiplex PCR to Detect the Seven Major Shiga Toxin–ProducingEscherichia coliBased on Genes That Code for Serogroup-Specific O-Antigens and Major Virulence Factors in Cattle Feces

Abstract: An 11-gene multiplex polymerase chain reaction (mPCR) was developed based on genes that code for serogroup-specific O-antigens and four major virulence factors (intimin, enterohemorrhagic hemolysin, and Shiga toxins [Stx] 1 and 2), to detect O157 and the "top six" non-O157 (O26, O45, O103, O111, O121, and O145) Shiga toxin-producing Escherichia coli (STEC). The assay specificity was validated with pure cultures of seven major STEC (185 strains), 26 other STEC (65 strains), non-STEC (five strains), and 33 strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 34 publications
1
72
1
Order By: Relevance
“…Although both O26 and O103 IMS beads appear to be relatively specific for the respective serogroups, colonies from O111 beads were often positive for the O103 gene (Table 1). This supports previous findings reported by Bai et al (2012). The detection of other STEC serogroups is likely due to nonspecific binding on the beads and subsequent use of a nondifferential medium.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although both O26 and O103 IMS beads appear to be relatively specific for the respective serogroups, colonies from O111 beads were often positive for the O103 gene (Table 1). This supports previous findings reported by Bai et al (2012). The detection of other STEC serogroups is likely due to nonspecific binding on the beads and subsequent use of a nondifferential medium.…”
Section: Discussionsupporting
confidence: 91%
“…This issue should be further investigated in order to characterize STEC risk associated with cattle production systems. Paddock et al (2012) and Bai et al (2012) concluded that multiplex PCR for STEC serogroups is most applicable for confirming putative isolates. Our results support their findings that culture-based methods using specific IMS beads followed by PCR confirmation of serogroup and virulence genes identifies a greater number of O-positive samples than using PCR directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 10 target colonies were picked per plate and heated at 958C in 50 ll of water for use as DNA template. Colonies were tested with the 11-plex PCR assay (4,9,53). Colonies positive for one of the EHEC-7 serogroup genes plus stx and eae were confirmed as an EHEC-7 strain, and the sample was counted as positive.…”
Section: Methodsmentioning
confidence: 99%
“…EIA or PCR methods to detect the toxin itself or the cognate genes are available (13). However, this provides little epidemiologic information, and neither does detection of other virulence factors such as the intimin gene, eae, or the hemolysin gene, ehxA (14)(15)(16). The current method employed by the USDA for food safety uses a multiplex PCR for stx 1 , stx 2 , and eae detection before using other genetic markers, such as variations in the wzx gene, to screen for O26, O45, O103, O111, O121, or O145 (17).…”
mentioning
confidence: 99%